Pengaruh Pemberian Susu Tinggi Protein terhadap Tingkat Nafsu Makan dan Kadar Glukosa Postprandial - Harna, Harna; M.Kusharto, Clara; Roosita, Katrin; Muh Asrul Irawan, Andi (Media Kesehatan Masyarakat Indonesia, 2018)
High protein milk is a complex food that contains several potential bioactive compounds that might effect on appetite control. However, the mechanism of high protein milk effect on appetite is still poorly understood in underweight adults. This study aimed to analyze the effect of high protein milk on appetite level and postprandial glucose. This study used experimental trial with design randomized controlled trial. The subjects were divided into two groups, 24 subjects in the treatment group and 23 subjects in the control group. Treatment group was given high protein milk and control group was given glucose. Subjective feelings including hunger, satisfaction, and desire to eat were evaluated using Visual Analogue Scale (VAS), which is analyzed in the incremental Area Under the Curve (iAUC). The results showed that there was a significant increase in iAUC value of hunger level in the treatment group compared with control (p<0.05), 8881±638.4 min.mm treatment group and 7297.8±439.6 min. mm control group. There was no significant difference in the level of satisfaction and desire to eat between the two groups (p>0.05). Postprandial glucose levels in the treatment group were significantly (p<0.05) lower than the control group. The study concluded that high protein milk intervention was increase hunger levels in underweight adults.